Investigating the Influence of Social Media Consumption on Punitive Attitudes Among a Sample of U.S. University Students. (February 2019) - Intravia, Jonathan
Prior research suggests that media consumption influences attitudes toward punitiveness. Traditionally, prior efforts have generally examined television news and crime-related programming. However, less is known whether more contemporary forms of media consumption, such as social media, are related to punitive attitudes. Using a multisite sample of more than 900 mostly young adults, the current study examines (a) the relationship between four types of social media consumption (overall, general news, crime-specific content, and punishment-specific content) on penal attitudes and (b) whether these relationships vary based on key characteristics. Results reveal that individuals who consume punishment-specific content on social media are significantly more likely to have stronger attitudes regarding the use of punishment and this relationship varies by fear of crime. Findings and directions for future research are discussed.